(untitled) (Global Journal of Human-Social Science, 2021)
This manuscript presents the ethnography of musical instruments in a Candomblé Ketu’s temple located in Brazil, specifically in Belém do Pará. The temple referenced in this essay is Ilè Àsé Iyá Ogunté, being led by the yalorixá Iyá Ejité. We will discuss to understand the connection of musical instruments with the songs performed in the ceremonies incorporated into the spatial organization of the terreiro, which seeks to reproduce the cosmogonic logic of the Orixás world, Òrun. In this sense, it was possible to present the sacredness of musical instruments to their players, exclusively male called Alabês, establishing a connection between Òrun and Ayê, a space where human beings live, offering a circularity that allows a constant exchange of fundamental energy of the universe, Axé, between humans and Orixás.